QUALITY ASSURANCE, SAFETY, AND ACCEPTABILITY OF STORED YELLOW LACTIC LAFUN: AN INDEX OF INCREASING IT SHELF LIFE - FAWOLE, ABOSEDE OYEYEMI; OGUNGBEMI, KUNLE; OKEDARA, EMMANUEL ODUNAYO; KOLAPO, ADELODUN LAWRENCE; AYODELE FATOKI, OLADOTUN (Innovare Journal of Agricultural Sciences, 2022)
Storability and shelf life of lafun has been a major challenge, especially in Nigeria, being a developing country that has limited or no storage facilities. Hence, necessitates a continuous search for remedies. This study thus evaluates the quality, safety, and acceptability of stored lactic lafun using different packaging materials. A 120 kg of cassava “TMS – IBA 01137” was procured from International Institute of Tropical Agriculture, Oyo state, Nigeria, and was fermented using Weissella koreensis stock culture obtained from University of Readings, United Kingdom. The fermented product was allowed for further processing; to obtain the end product “Lactic lafun.” The samples were then introduced into four different packaging materials which include Ziploc transparent bag, Ziploc opaque bag, vacuum sealed transparent bag, and vacuum sealed opaque bag for 90 days. Physicochemical, pasting, sensory, and microbial analyses were carried out every 30 days. The results showed for microbial analysis, showed that the Ziploc materials contain high microbial count as it has the highest count of bacteria (6.8–7.5 LogCFU) and fungi (7.0–9.0 LogCFU) throughout the storage period. The proximate analysis also showed increase in moisture content (p<0.05) in transparent packaging materials when compared with their baseline sample at day 0 (3.5±0.09) whereas, there was no significant changes in the ash, fiber, CHO, and lipid across all the samples. The carotenoid content level decreased significantly (0.212±0.04) in the transparent packaging materials with increasing days of storage when compared to the baseline sample (1.977±0.012). There is a significant reduction (p<0.05) in the hydrogen cyanide of the lafun sample when compared to the baseline. The organoleptic property showed no significant difference in the acceptability of all the samples. It can, therefore, be concluded that lactic lafun produced from yellow cassava stored in opaque materials presents a viable and sustainable means of tackling carotenoid deficiencies and spoilage of lafun over a long period of time.